2019
DOI: 10.1088/1755-1315/290/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Concrete, Sustainability and Limit States

Abstract: Efficient sustainability management of concrete structures requires the use of tools which allow material, technological and construction variants to be quantified. The present contribution, apart from discussing the issue of sustainability of concrete structures, focuses on the quantification of concrete resistance to degradation. An indicator expressing quality, with regard to sustainability, is determined using information on concrete performance characteristics, service life and eco-costs, enabling the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This combined indicator was recently presented in, e.g. Hrabová et al (2019), and Konečný et al (in revision). Indicator kSB is a normalized form of the Building Material Sustainability Potential (BMSP) defined previously by Müller (2013).…”
Section: The Limit State Concept From the Perspective Of Sustainabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…This combined indicator was recently presented in, e.g. Hrabová et al (2019), and Konečný et al (in revision). Indicator kSB is a normalized form of the Building Material Sustainability Potential (BMSP) defined previously by Müller (2013).…”
Section: The Limit State Concept From the Perspective Of Sustainabilitymentioning
confidence: 86%
“…elements of social responsibility, and therefore SLS, ULS and L also fall into this category -usually being understood and utilized as basic safety and serviceability criteria as well. Details concerning this class of limit equations and their practical utilization have not yet been specified in the fib Model Code 2010 (2012) or anywhere else to the best knowledge of the authors; an overview of the equations and a short literature review can be found in Hrabová et al (2019).…”
Section: The Limit State Concept From the Perspective Of Sustainabilitymentioning
confidence: 99%
“…Nevertheless, the expenses should be inspected not only with respect to the manufacturing cost but also in the context of the whole life span, which is, in the case of bridges, 100 years. Convincing quantification of all relevant expenses, together with environmental impact, i.e., life cycle analysis, is the objective of many research tasks [44,45]. Their application in the case of bridge beams is the object of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Concrete is one of the important construction materials that is widely used in building structures due to its availability, low cost, and workability [1,2]. Because concrete under load pressure can fail, determining its compressive strength plays a vital role in judging its quality.…”
Section: Introductionmentioning
confidence: 99%